Analisis Faktor yang Memengaruhi Keputusan Agresivitas Transfer Pricing - Ali Sandy Mulya (Penerbit Goodwood, 2022)
Purpose: To analyze the factors that influence a company's decision to carry out transfer pricing aggressiveness. The factors used in this research are profitability, capital intensity ratio, executive risk preference, transfer pricing aggressiveness, and tax burden. Method: The method used in this study is a quantitative research method. The research data uses secondary data, which is obtained from financial reports. The analytical method used in this study is path analysis using Warp Partial Least Squares. Result: All factors used in this study have no effect on transfer pricing aggressiveness, including those mediated by the tax burden. Except for executive risk preferences which directly affect the aggressiveness of transfer pricing. Executives who have a risk taker preference have more courage in determining a policy even though the risk is high. However, risk takers with their courage are also required to generate higher cash flows. This is done to balance the risks arising from the courage to take an action or decision. Among the various executive decisions is the decision to carry out aggressive transfer pricing. One of the ways that executives do this is by placing trusted people who have the expertise to observe and create tax avoidance schemes according to the wishes of the executive (Dyreng et al., 2010). Limitations: This study only uses secondary data from manufacturing companies whose answers do not yet show the overall condition of companies in Indonesia Contribution: Companies should consider carefully if they want to carry out aggressive transfer pricing legally and in accordance with applicable tax regulations